Airwake Characteristics of NATO-Generic Destroyer: A Numerical Study - Sari, S.; Dogrul, A.; Bayraktar, S. (ISFAHAN UNIV TECHNOLOGY, 2025)
This paper presents a numerical investigation of the air wake around a generic surface combatant ship called NATO-Generic Destroyer (NATO-GD). Naval surface combatants with flight decks must be designed taking aerodynamic concerns into account. Most of the previous studies have employed the Simple Frigate Shape (SFS) and its modified version (SFS2) to investigate the airwake. However, these generic geometries do not accurately represent modern warship designs. To address this, a modern geometry called NATO-GD proposed by the NATO Research Task Group, which represents the features of a modern destroyer, was utilized in the present work. The objective is to examine the air wake on the helicopter deck to ensure the safe operation of air vehicles such as helicopters and drones. The three-dimensional, transient airflow around the ship was solved using the unsteady Reynolds-Averaged Navier-Stokes (URANS) and Detached Eddy Simulation (DES) turbulence models. Besides, the effect of inflow was investigated by comparing uniform velocity inlet and atmospheric boundary layer (ABL) for various wind-over-deck (WOD) angles. The numerical approach was verified for the URANS turbulence model using the Grid Convergence Index (GCI) method. The numerical uncertainty was calculated with four different methods and the uncertainty was found between 1.6% and 2.1%. A detailed discussion of the flow field above the flight deck was conducted to compare the URANS and DES models fairly. It was concluded that employing the ABL profile as a boundary condition is more suitable for achieving accurate ship aerodynamics calculations. The ABL velocity profile makes a significant difference in the velocity components. According to the URANS results, these deviations are found as 8.23% in the x-component, 1.25% in the y-component and 4.89% in the z-component. The deviations were calculated using the root mean square error (RMSE) method. Furthermore, although the numerical results of the URANS and DES models were similar at some points, detailed flow field analysis is only possible with the DES results to determine safe approach patterns for air vehicles. Various wind speeds, directions, and the resulting wake structures were tested to analyze the wake behavior over the helicopter deck under different air conditions. When the wind comes from the port side with 15 degrees (R15) it wind changes the intense turbulence region and creates a low turbulence area on the starboard side while R30 wind causes small scale vortices breaking this region.
Keywords: DES; GCI; NATO-GD; Ship Airwake; Turbulence; URANS; SHIP-AIRWAKE; SIMULATIONS; HELICOPTER; PROPULSION; Thermodynamics; Mechanics